Procalcitonin kinetics to guide sequential invasive-noninvasive mechanical ventilation weaning in patients with acute exacerbation of chronic obstructive pulmonary disease and respiratory failure: procalcitonin's adjunct role. Issue 1 (1st January 2021) - Lin, Shao-Hua; He, Ying-ping; Lian, Jun-Jie; Chu, Cun-Kun
ABSTRACT: How to identify the optimum switch point of sequential invasive and noninvasive ventilation is the focus of clinical attention on the patients suffering from acute exacerbation of chronic obstructive pulmonary disease (AECOPD) complicated by acute respiratory failure (ARF). This study aims to explore the clinical significance of taking the change rate of procalcitonin (PCT) as identifying the timing of weaning on the mechanical ventilation for the patients of AECOPD followed by ARF as a complication. There were altogether 140 patients of AECOPD complicated with ARF, who were randomly selected and divided into a study group and a control group respectively. A change rate of serum PCT level exceeding 50% was taken as the switch point selection of tracheal intubation removal for the patients of the study group, while the 'pulmonary infection control (PIC) window' was done for those in the control group. With CRP, IL-6, TNF-a, PaCO2, PaO2, and Lac having been detected before and after treatment to them all, clinical indexes were obtained and compared between these two groups. The CRP, TNF-a, and IL-6 levels of the patients in the study group after treatment ( p < 0.05 ) were lower than those in the control group. There was no significant difference in PaCO2, PaO2, and Lac between these two groups before and after treatment ( p > 0.05 ). Even so, some other indexes available for the study group of patients were found to be lower than those for the control group ( p < 0.05 ) in the following aspects: duration of invasive ventilation support, total time of mechanical ventilation support, incidence rate of ventilator-associated pneumonia, 48-hour reintubation rate, incidence rate of upper gastrointestinal bleeding, hospitalization time of critical respiratory illness, total hospitalization time, RICU treatment cost, total treatment cost, and mortality. It is preferable to take the change rate of PCT level exceeding 50% as the switch point of weaning time in sequential mechanical ventilation rather than the PIC window. Abbreviations AECOPD: acute exacerbation of chronic obstructive pulmonary disease; ARF: acute respiratory failure; PCT: procalcitonin; PaO2 : the oxygen partial pressure; PaCO2 : the partial pressure of carbon dioxide; TNF-a: serum tumor necrosis factor-a; IL-6: interleukin-6; CRP: serum C-reactive protein; PIC window: pulmonary infection control window; RICU: respiration and intensive care unit